Gestión del riesgo cambiario: aplicación a una empresa exportadora peruana - Lizarzaburu, Edmundo R. (2013)
This paper aimks to assess and quantify the exchange risk in an exporting firm. It begins by explaining currency risk, followed by a qualitative analysis of the dollar exchange rate volatility against the Nuevo Sol. This analysis is relevant, because each country has different exchange characteristics, which in the end impacts on the currency flow and exchange rate, among others. It also explores other financial instruments such as factoring with recourse and Non-Deliverable Forward as coverage alternatives. The range for the analysis is from January 2010 to December 2012.